I know how to do it in normal Euclid geometry, but is it possible to do it with vector algebra?

  • $\begingroup$ The translation of the claim is: Given $a,b,c$ there exists $h$ such that $\langle h-a,c-b\rangle=\langle h-b,a-c\rangle=\langle h-c,b-a\rangle=0$. Or: If $h$ is such that $\langle h-a,c-b\rangle=\langle h-b,a-c\rangle=0$, then also $\langle h-c,b-a\rangle=0$. Can you find a proof? You may assume that $h=xa+yb+zc$ with $x,y,z\in\mathbb R$ and $x+y+z=1$. $\endgroup$ – Hagen von Eitzen Dec 10 '12 at 16:44
  • $\begingroup$ @HagenvonEitzen Thanks, but I don't quite follow your notation, could you please explain further? $\endgroup$ – qed Dec 10 '12 at 17:27
  • $\begingroup$ Ah, maybe the use of $\langle,\rangle$ for scalar (or dot) product is unusual for you ... $\endgroup$ – Hagen von Eitzen Dec 10 '12 at 17:59
  • $\begingroup$ @HagenvonEitzen, Oh, that's dot product, i see. Thanks! $\endgroup$ – qed Dec 10 '12 at 18:48

Assume that the altitudes $AI$ and $CJ$ intersect at point O. We need to prove that $BO$ is perpendicular to $AC$.

$\vec{BJ}$ is the projection of $\vec{BO}$ onto $\vec{BA}$. Hence:

$$ \vec{BJ} = \frac{\vec{BO}\cdot\vec{BA}}{||\vec{BA}||^2}\vec{BA} \quad (1) $$

However, $\vec{BJ}$ is also the projection of $\vec{BC}$ onto $\vec{BA}$. Hence:

$$ \vec{BJ} = \frac{\vec{BC}\cdot\vec{BA}}{||\vec{BA}||^2}\vec{BA} \quad (2) $$

From (1) and (2) we have that $\vec{BO}\cdot\vec{BA} = \vec{BC}\cdot\vec{BA}$. In the same way working with $\vec{BO}$ on $\vec{BC}$ we get $\vec{BO}\cdot\vec{BC} = \vec{BA}\cdot\vec{BC}$. Hence we have $\vec{BO}\cdot\vec{BA} = \vec{BC}\cdot\vec{BA} = \vec{BO}\cdot\vec{BC}$. Now:

$$ \vec{BO} \cdot \vec{AC} = \vec{BO} \cdot (\vec{AB} + \vec{BC}) = \vec{BO} \cdot \vec{BC} - \vec{BO} \cdot \vec{BA} = 0 $$

Hence $\vec{BO}$ and $\vec{AC}$ are perpendicular.


Denote the three vertices of the triangle by three column vectors $\mathbf{u}, \mathbf{v}, \mathbf{w} \ (\in\mathbb{R}^2)$ and the orthocenter by $\mathbf{x}$. By definition, $\mathbf{x}$ must satisfies $$ \begin{cases} (\mathbf{v}-\mathbf{w})\cdot(\mathbf{x}-\mathbf{u})=0\\ (\mathbf{w}-\mathbf{u})\cdot(\mathbf{x}-\mathbf{v})=0\\ (\mathbf{u}-\mathbf{v})\cdot(\mathbf{x}-\mathbf{w})=0 \end{cases} \ \Rightarrow \begin{cases} (\mathbf{v}-\mathbf{w})\cdot\mathbf{x}=(\mathbf{v}-\mathbf{w})\cdot\mathbf{u}\\ (\mathbf{w}-\mathbf{u})\cdot\mathbf{x}=(\mathbf{w}-\mathbf{u})\cdot\mathbf{v}\\ (\mathbf{u}-\mathbf{v})\cdot\mathbf{x}=(\mathbf{u}-\mathbf{v})\cdot\mathbf{w} \end{cases} $$ This can be rewritten in the matrix form of $A\mathbf{x}=\mathbf{b}$: $$ \underbrace{\begin{bmatrix}(\mathbf{v}-\mathbf{w})^T\\ (\mathbf{w}-\mathbf{u})^T\\ (\mathbf{u}-\mathbf{v})^T\end{bmatrix}}_{A} \ \mathbf{x} = \underbrace{\begin{bmatrix} (\mathbf{v}-\mathbf{w})\cdot\mathbf{u}\\ (\mathbf{w}-\mathbf{u})\cdot\mathbf{v}\\ (\mathbf{u}-\mathbf{v})\cdot\mathbf{w} \end{bmatrix}}_{\mathbf{b}} $$ So, the remaining question is, does there exist a unique solution for $A\mathbf{x}=\mathbf{b}$? Note that $A$ is a 3x2 matrix and $\mathbf{x}$ is a 2-vector, so the above system has three equations in two unknowns, i.e it is overdetermined. Can you show that each one of these three equations is a linear combination of the other two? Is it possible to remove one row from $A$, so that the remaining 2x2 submatrix is invertible?


I am giving below a rather simple solution using vectors. Please make your own figure as I could not put in the same. Also treat small letters $a$, $b$, and $c$ as vectors. Write to me if you need more explanation.

Let $ABC$ a be triangle, let the perpendicular from $A$ to $BC$ meet $BC$ at $D$, and let the perpendicular from $B$ to $AC$ meet $AC$ at $E$. Let the lines $AD$ and $BE$ intersect at $O$. Let $O$ be the origin.

To prove: if we join $C$ and $O$ and extend it up to meet $AB$ at $F$, then $CF$ is perpendicular to $AB$.

Now, $CB$ is perpendicular to $OA$ (part of $AD$).

Therefore (1) $(c-b) \cdot a = 0$, since $(c-b)$ is the vector $CB$ and $OA$ is the vector $a$.

Similarly, $CA$ is perpendicular to $OB$ (part of $BE$).

Therefore, (2) $(c-a) \cdot b = 0$.

From (1), we obtain (3) $c \cdot a - b \cdot a = 0$.

From (2), we obtain (4) $c \cdot b - a \cdot b = 0$.

Subtracting (3) from (4), we get

$(c \cdot b - a \cdot b) – (c \cdot a - b \cdot a) = 0$

$\Rightarrow (c \cdot b - c \cdot a) – (a \cdot b - b \cdot a) = 0$

$\Rightarrow (c \cdot b - c \cdot a) = 0$, since $a \cdot b = b \cdot a$

$\Rightarrow (b - a) \cdot c = 0$.

Therefore $BA$ is perpendicular to $OC$ or $FC$. Therefore $O$ is the orthocenter of the triangle $ABC$ from which the three altitudes pass.


enter image description here

Let's use the figure above in our approach.

Let be $|\vec{b}|=b$, $|\vec{c}|=c$, and $\vec{b}\cdot\vec{c}= m$. The orthocenter can be calculated in two ways: $$O=A+\overrightarrow{AB}+\lambda\overrightarrow{HB}\quad (1)$$ or $$O=A+\overrightarrow{AC}+\mu\overrightarrow{JC}\quad (2)$$ But $$\overrightarrow{HB}=\vec{c}-[\frac{(\vec{b}\cdot\vec{c})}{b}]\frac{\vec{b}}{b}\quad (3)$$ and $$\overrightarrow{JC}=\vec{b}-[\frac{(\vec{b}\cdot\vec{c})}{c}]\frac{\vec{c}}{c}\quad (4)$$ If we substitute $(3)$ and $(4)$ in $(1)$ and $(2)$, we get: $$O=A+\vec{c}+\lambda[\vec{c}-(\frac{m}{b^2})\vec{b}]\quad (5)$$ and $$O=A+\vec{b}+\mu[\vec{b}-(\frac{m}{c^2})\vec{c}]\quad (6)$$ Using equations $(5)$ and $(6)$ we get: $$\vec{c}+\lambda[\vec{c}-(\frac{m}{b^2})\vec{b}]=\vec{b}+\mu[\vec{b}-(\frac{m}{c^2})\vec{c}]\Rightarrow$$


As $\vec{b}$ and $\vec{c}$ are linearly independent we can solve equation $(7)$ and we get: $$\mu=\frac{(m-b^2)}{c^2b^2-m^2}c^2$$

Now we can express $\overrightarrow{AO}$ as


If $\overrightarrow{AO}\cdot\overrightarrow{BC}=0$ then we can conclude that the three altitudes are concurrent.

So $$\overrightarrow{AO}\cdot\overrightarrow{BC}=(\vec{b}+\frac{(m-b^2)}{c^2b^2-m^2}c^2[\vec{b}-(\frac{m}{c^2})\vec{c}])\cdot(\vec{b}-\vec{c})\Rightarrow$$

$$\Rightarrow \overrightarrow{AO}\cdot\overrightarrow{BC}=b^2+\frac{(m-b^2)}{c^2b^2-m^2}c^2(b^2-\frac{m^2}{c^2})-m+\frac{(m-b^2)}{c^2b^2-m^2}c^2(-m+m)\Rightarrow$$

$$\Rightarrow \overrightarrow{AO}\cdot\overrightarrow{BC}=b^2+(m-b^2)-m+0\Rightarrow$$

$$\Rightarrow \overrightarrow{AO}\cdot\overrightarrow{BC}=0$$

Therefore the three altitudes are concurrent at point $O$.


Triangle vertices O, vector a and vector b Intersection of perpendiculars from a and b is H, vector h from O, say. We need to show that h is perpendicular to vector b - a, the side of the triangle opposite to O.

Now $(h - a).b = 0$ as line from vertex A to H is perpendicular to b and $(h - b).a = 0$ as line from vertex B to H is perpendicular to a

Removing brackets: $h.a = h.b = a.b$ So$ h.(b-a) = h.b - h.a =0$ and$ h$ is perpendicular to $b - a$, the third side of the triangle. QED.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.